2022
DOI: 10.21105/joss.04237
|View full text |Cite
|
Sign up to set email alerts
|

rabpro: global watershed boundaries, river elevation profiles, and catchment statistics

Abstract: River and Basin Profiler (rabpro) is a Python package to delineate watersheds, extract river flowlines and elevation profiles, and compute watershed statistics for any location on the Earth's surface. As fundamental hydrologically-relevant units of surface area, watersheds are areas of land that drain via aboveground pathways to the same location, or outlet. Delineations of watershed boundaries are typically performed on digital elevation models (DEMs) that represent surface elevations as gridded rasters. Depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Few bank erosion studies reported bankfull or maximum discharges, and many of the rivers in both our Arctic and meta‐analysis of published erosion rates are ungauged or lack reliable stream flow data for the reaches of interest. Therefore, we extracted the long‐term average (1960–2015) of the FLO1K annual maximum monthly discharge (Barbarossa et al., 2018) using the Python package rabpro (Schwenk et al., 2022) https://doi.org/10.21105/joss.04237. The annual maximum monthly discharge captures both geomorphically relevant discharges that occur for sufficient durations to be effective and avoids biases of short‐lived outliers potentially captured in the annual maximum daily discharge.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few bank erosion studies reported bankfull or maximum discharges, and many of the rivers in both our Arctic and meta‐analysis of published erosion rates are ungauged or lack reliable stream flow data for the reaches of interest. Therefore, we extracted the long‐term average (1960–2015) of the FLO1K annual maximum monthly discharge (Barbarossa et al., 2018) using the Python package rabpro (Schwenk et al., 2022) https://doi.org/10.21105/joss.04237. The annual maximum monthly discharge captures both geomorphically relevant discharges that occur for sufficient durations to be effective and avoids biases of short‐lived outliers potentially captured in the annual maximum daily discharge.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
“…Second, where available, we used the reported slopes from the global data set of Lin et al (2020). Finally, we used the rabpro software (Schwenk et al, 2022) https://doi.org/10.21105/joss.04237 to calculate slope along reaches where data were unavailable from the other data sources. The errors associated with slope estimates are discussed in Supporting Information S1 (Text S2).…”
Section: Global Compilation Of Published Erosion Rates and Watershed ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Few bank erosion studies reported bankfull or maximum discharges, and many of the rivers in both our Arctic and meta-analysis of published erosion rates are ungauged or lack reliable stream flow data for the reaches of interest. Therefore, we extracted the long-term average (1960 -2015) of the FLO1K annual maximum monthly discharge (Barbarossa et al, 2018) using the Python package rabpro (J Schwenk et al, 2022). The annual maximum monthly captures both geomorphically relevant discharges that occur for sufficient durations to be effective and avoids biases of short-lived outliers potentially captured in the annual maximum daily discharge.…”
Section: Analysis Of Remotely Sensed and Published Erosion Ratesmentioning
confidence: 99%
“…To compute basin characteristics needed for gage selection and analysis (e.g., permafrost coverage, topographic slope, aspect, and others) we used the River and Basin Profiler (rabpro, Schwenk et al, 2022). Rabpro automatically delineates watersheds by snapping gage points to appropriate MERIT-Hydro (Yamazaki et al, 2019) flowlines and performing digital-elevation model-based pixeltracing to identify all pixels draining to the snapped location.…”
Section: Study Site and Streamflow Gage Selectionmentioning
confidence: 99%